2018
DOI: 10.18781/r.mex.fit.1708-5
|View full text |Cite
|
Sign up to set email alerts
|

Escala diagramática para cuantificación de la severidad de la roya en hojas de teca

Abstract: <p>La roya de la teca (<em>Tectona grandis</em>), causada pelo fungo <em>Olivea tectonae</em>, se ha presentado en varias regiones de Brasil en casos graves que conducen a la caída prematura de las hojas e incluso la muerte de la planta. Sin embargo, todavía no existe un método estándar para la evaluación de la severidad de la enfermedad en el campo. El objetivo de este estudio fue desarrollar y validar una escala diagramática para cuantificar la severidad de la roya en hojas de t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…A b value equal to 1 was obtained by seven raters using the seven-and nine-class scales and by ten raters using the eight-class scale, meaning that 58 and 83% of the evaluations were statistically significant. Cristiane-Delmadi et al (2018) highlighted that the degree of subjectivity that conditions the use of diagrammatic scales, as well as of most of the methods applied to quantify the damage caused by pests and diseases, can be minimized by training the raters.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A b value equal to 1 was obtained by seven raters using the seven-and nine-class scales and by ten raters using the eight-class scale, meaning that 58 and 83% of the evaluations were statistically significant. Cristiane-Delmadi et al (2018) highlighted that the degree of subjectivity that conditions the use of diagrammatic scales, as well as of most of the methods applied to quantify the damage caused by pests and diseases, can be minimized by training the raters.…”
Section: Resultsmentioning
confidence: 99%
“…In general, most diagrammatic scales have from five to eight classes (Yadav et al, 2013;González-Domínguez et al, 2014;Vieira et al, 2014;Cristiane-Delmadi et al, 2018). Campbell & Madden (1990) concluded that the number of classes should not be too low (fewer than four), because the resolution power would also be low, or too high (more than ten), because it would be difficult to select the most appropriate class.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oleh sebab karakter serangan hama maupun penyakit dapat berbeda-beda satu sama lainnya, maka disarankan untuk mengembangkan alat ukur yang spesifik untuk hama atau penyakit tertentu. Salah satu alat ukur yang telah dikembangkan adalah diagram berskala yang dikembangkan oleh Cristiane-Delmadi et al (2018) untuk mengukur keparahan penyakit karat pada daun jati. Pengembangan alat ukur tersebut berhasil meningkatkan akurasi dalam pengukuran keparahan penyakit karat pada daun jati.…”
Section: Nilai Kejadian Dan Keparahan Gejalaunclassified
“…efecto antagonista de los consorcios exitosos formados, como para el análisis de la capacidad fertilizante, se utilizaron 30 plantas, 27 plantas para los tratamientos, y tres plantas como controles negativos (Fotoohiyan et al, 2017). Finalmente, se analizó la incidencia, la severidad de la MV y el efecto biofertilizante mediante la comparación de los resultados del área foliar, porcentaje de humedad y la longitud de las raíces y tallos (Delmadi, De Pieri, Porcena, y Furtado, 2018). Estos resultados fueron evaluados estadísticamente con el análisis de varianza (ANOVA) y pruebas post hoc Tukey con un nivel de significancia de 95%.…”
Section: áRea De Propagación De Gypsophilaunclassified